Determining the Optimal Replenishment Policy for K-24 Pharmacy Pondok Pinang - Gumilang, Giusti Reza; Basri, Mursyid Hasan (Journal of Business and Management, 2012)
This research discusses about the regulation of product replenishment in K-24 Pharmacy Pondok Pinang. The main problem is that the total cost to replenish 4 products with highest value is too high. This may because of the existing regulation isn’t optimal enough. The amount of stock in an order and the range time between orders is too flexible, and the lead time from ordering to receiving the product is also small, allowing the firm to order new supply almost in any day, without considering the ordering cost. The author decides to determine the optimal regulation for the future of product replenishment system in K-24 Pharmacy Pondok Pinang. Therefore, the author needs to find new strategies to find the right regulation of product replenishment system that can reduce the total cost. Design/methodology/approach: The theories used are demand forecasting to find the targeted year’s estimated demand, continuous and periodic review policy with the ROP, EOQ, OUL and SS inside it to find whether the product should order with fixed quantity or range of time, business process to know the roles and help the implementation plan.Finding: The end of this research shows that K-24 Pharmacy Pondok Pinang should use the continuous review policy as their replenishment policy to minimum their total cost in the next years. Existing regulation is too flexible, the firm can order supplies with any quantity in any time, it may good to avoid lost sales but not for their costs.Research limitations/implications: This research only focus to the inventory management of the 4 chosen product, the year used for observation is from the last 2 years ( and 2011), and the variable of inflation and expired date will be ignored.Practical Implications: There are changes in system of recording the stock and sales to support the proposed replenishment strategy.The outcome of this research is Replenishment Strategy in form of new Review Policy to apply to the K-24 Pharmacy Pondok Pinang’s inventory management that can reduce the total cost.  Originality/value: This research has an outcome which is Replenishment Strategy that can reduce the total cost.Keywords: Inventory Management, Stock Replenishment Policy, Demand Forecast, PharmacyCategory: Performance Management; Operation.